The National Institute of Environmental Health Sciences Superfund Research Program: a model for multidisciplinary training of the next generation of environmental health scientists. - Carlin, Danielle J.; Henry, Heather; Heacock, Michelle; Trottier, Brittany; Drew, Christina H.; Suk, William A. (Reviews on Environmental Health, 2018)
The National Institute of Environmental Health Sciences (NIEHS) Superfund Research Program (SRP) funds university-based, multidisciplinary research on human health and environmental science and engineering with the central goals to understand how hazardous substances contribute to disease and how to prevent exposures to these environmental chemicals. This multi-disciplinary approach allows early career scientists (e.g. graduate students and postdoctoral researchers) to gain experience in problem-based, solution-oriented research and to conduct research in a highly collaborative environment. Training the next generation of environmental health scientists has been an important part of the SRP since its inception. In addition to basic research, the SRP has grown to include support of broader training experiences such as those in research translation and community engagement activities that provide opportunities to give new scientists many of the skills they will need to be successful in their field of research. Looking to the future, the SRP will continue to evolve its training component by tracking and analyzing outcomes from its trainees by using tools such as the NIEHS CareerTrac database system, by increasing opportunities for trainees interested in research that goes beyond US boundaries, and in the areas of bioinformatics and data integration. These opportunities will give them the skills needed to be competitive and successful no matter which employment sector they choose to enter after they have completed their training experience.